2017
DOI: 10.4236/jtr.2017.54024
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Annual Incidence of Carbapenem Resistant among Gram Negative Bacilli in a Large Teaching Hospital in Makah City, Saudi Arabia

Abstract: Objective: To detect the prevalence of carbapenem resistance among Gram negative bacilli at the Al-Noor Specialist Hospital in the western part of Saudi Arabia. Materials and Methods: This study was conducted in the Microbiology department, Al-Noor Specialist Hospital, Makah city, Saudi Arabia. The clinical samples were collected from admitted patients in the wards, Intensive Care Units (ICUs), urology unit and surgery unit, these samples included blood, urine, sputum, pus and wound. The identification and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
2
8
1
Order By: Relevance
“…While S.marcescens showed complete resistance to all antibiotics under study. The results were agreed with Faidah [17] for Amikacin, while disagreed with Tetracycline, Ceftazidime, Gentamycin, Impenem, Trimethoprim and Cefotaximeas also disagreed with Ahmed and Aziz [14] for Amoxicillin and Cefotaxime. K. pneumoniae was show complete resistance against all antibiotic, these results were consistent with Hashim [11]forAmoxicillin and Tetracycline (100%), but disagreed with the following antibiotic: Amikacin, Cefotaxime, Trimethoprim, Tobramycin, and Gentamycin which found no sensitivity to these antibiotic by bacteria (0%).…”
Section: Antibiotic Susceptibility Testsupporting
confidence: 66%
“…While S.marcescens showed complete resistance to all antibiotics under study. The results were agreed with Faidah [17] for Amikacin, while disagreed with Tetracycline, Ceftazidime, Gentamycin, Impenem, Trimethoprim and Cefotaximeas also disagreed with Ahmed and Aziz [14] for Amoxicillin and Cefotaxime. K. pneumoniae was show complete resistance against all antibiotic, these results were consistent with Hashim [11]forAmoxicillin and Tetracycline (100%), but disagreed with the following antibiotic: Amikacin, Cefotaxime, Trimethoprim, Tobramycin, and Gentamycin which found no sensitivity to these antibiotic by bacteria (0%).…”
Section: Antibiotic Susceptibility Testsupporting
confidence: 66%
“…This was higher than that the results of Oberoi et al [20] who reported 8.79% of coexistence, and less than [21] who reported 48.7% of the total β-lactamases. In Saudi Arabia, phenotypic studies from Makkah reported positive MBLs production with a range between 38% and 48% [22,23]. In our study, the phenotypic coexistence of ESBLs and MBLs was common in K. pneumonia (15.4%), E. coli (7.7%), and Ps.…”
Section: Discussionsupporting
confidence: 50%
“…Carbapenemase-producing Enterobacteriaceae such as KPC and New Delhi metallo-β-lactamase NDM have achieved global dissemination and pose a serious threat to human life [ 8 , 20 ]. The Kingdom of Saudi Arabia has reported a rise in carbapenem-resistant Enterobacteriaceae , mostly from Riyadh [ 15 , 21 , 22 , 23 , 24 ] and Makkah [ 14 , 25 ].…”
Section: Discussionmentioning
confidence: 99%